2003
DOI: 10.1007/bf03018732
|View full text |Cite
|
Sign up to set email alerts
|

Edrophonium effectively antagonizes neuromuscular block at the laryngeal adductors induced by rapacuronium, rocuronium and cisatracurium, but not mivacurium

Abstract: P Pu ur rp po os se e: : To examine the efficacy of antagonism of rapacuronium-, mivacurium-, rocuronium-and cisatracurium-induced neuromuscular block at the laryngeal adductors (LA). M Me et th ho od ds s: :One hundred four patients were randomly assigned to one of eight study groups. They either received rapacuronium 1.5 mg·kg ) at 10% recovery of the first twitch (T1) of train-of-four (TOF) at the LA or were allowed to recover spontaneously from neuromuscular block. The effect of antagonism on speed of reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Two studies used the predefined endpoint TOF 0.9 . Both studies also presented time to TOF 0.7, which was the endpoint in all other studies, apart from two trials where TOF 0.75 was used as endpoint …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Two studies used the predefined endpoint TOF 0.9 . Both studies also presented time to TOF 0.7, which was the endpoint in all other studies, apart from two trials where TOF 0.75 was used as endpoint …”
Section: Resultssupporting
confidence: 93%
“…Sixteen randomized controlled studies with data from 546 patients were included . Six studies compared spontaneous recovery with both neostigmine and edrophonium reversal .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One new RCT corroborates findings reported in the original Guidelines regarding the efficacy of edrophonium to antagonize the effects of neuromuscular blocking agents (e.g., rocuronium, cisatracurium, rapacuronium) when compared with spontaneous recovery (Category A3-B evidence). 71 The original Guidelines indicated that neostigmine is effective for the antagonism of residual neuromuscular blockade (Category A1-B evidence); new literature is insufficient to further evaluate these findings. The original Guidelines reported an increased frequency of postoperative emetic episodes with the use of neostigmine (Category A1-H evidence); new literature is insufficient to further evaluate this finding.…”
Section: Antagonism Of the Effects Of Sedatives Analgesics And mentioning
confidence: 99%